(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Now a dayâ€™s images are essential thought and lasting impression at mass communication. The awesome thing is that image compression also essential for its applications such as transmission and store in database. An endeavour of this paper to give a guideline for an assortment of images, compression, need for compression, compression principles, compression techniques, classifications of compression techniques, and several of algorithms for image compression. And also study of this review to choose a engender guidelines to get the best compression algorithm for an images to compress, communicate (transmit) and how the images, compression and its algorithms are helpful to mass communication. Â Key Words: - Image, Compression, Compression Techniques, algorithms.